Pemetaan Fungsi Platforn E-Portofolio Untuk Perkuliahan di Jurusan Kurikulum dan Teknologi Pendikan Fakultas llmu Pendidikan Universitas Negeri Jakarta - Nurdin Ibrahim; R.A. Hirmana Wargahadibrata (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2016)
he purpose of this study is the to Mapping the three characteristic of the e- portfolios platform. This research was conducted by the design and development research method by using two methodologies: (1)Tool Use, (2) Model Development. This study collecting various types of platforms specialized to the development e- portfolios and will do a mapping of the function of the platform that has been ellected. To achieve the goal the first year will be used Expert Reviews surveys method The experts will give ratings to the three pieces of E-portfolio Platform installedin www.eportofolio.ac.id, namely Elgg, Moodle and Mahara. Based on these results, the researchers conclude Mahara Platform is the appropriate platform to be used in the learning process. It is supported ratings obtained from the experts.